A georeferenced dataset of heavy metals occurrence in the soils of the Yangtze River Basin, China - Yifan Sun; Dongsheng Liu; Long Xie; Zheng Gao; Qi Zhang; Luqi Wang; Sen Li (Geoscience Data Journal)
Abstract Understanding the fine‐scale spatial distribution of heavy metal contamination is crucial for effective environmental capacity control and targeted treatment of polluted areas. This article presents the latest dataset on the occurrence of common heavy metals in the soils of the Yangtze River Basin. The dataset was compiled by reviewing peer‐reviewed literature published between 2000 and 2020. Rigorous quality control procedures were employed to ensure the accuracy of the data, including the extraction of detailed geographic locations and concentrations of heavy metals. The dataset includes 7867 records of heavy metal occurrences (Zn: 1045, Cu: 1140, Pb: 1261, Cr: 980, Cd: 1242, Ni: 649, As: 821, Hg: 729) in the soils of the Yangtze River Basin, distributed at four scale levels: province, prefecture, county, and township or finer. The results indicate that the distribution of heavy metal concentrations is relatively scattered, with higher concentrations in cities and regions with developed industry and agriculture. Cd has the highest exceedance rate (33.90%), indicating significant local contamination. Heavy metals, such as Zn at 11.96%, Ni at 12.63%, and As at 9.74%, also exceeded standard levels at certain sampling points. Cr had the lowest exceedance rate of 1.33%. This updated dataset provides essential information on the current status of heavy metals contamination in the soils of the Yangtze River Basin. It can be used for further ecological and health risk assessments and for developing strategies to remediate and prevent heavy metal contamination in the region.